The third P-loop domain in cytoplasmic dynein heavy chain is essential for dynein motor function and ATP-sensitive microtubule binding. - Silvanovich, A.; Li, M.G.; Serr, M.; Mische, S.; Hays, T.S. (Molecular Biology of the Cell, 2003)
Sequence comparisons and structural analyses show that the dynein heavy chain motor subunit is related to the AAA family of chaperone-like ATPases. The core structure of the dynein motor unit derives from the assembly of six AAA domains into a hexameric ring. In dynein, the first four AAA domains contain consensus nucleotide triphosphate-binding motifs, or P-loops. The recent structural models of dynein heavy chain have fostered the hypothesis that the energy derived from hydrolysis at P-loop 1 acts through adjacent P-loop domains to effect changes in the attachment state of the microtubule-binding domain. However, to date, the functional significance of the P-loop domains adjacent to the ATP hydrolytic site has not been demonstrated. Our results provide a mutational analysis of P-loop function within the first and third AAA domains of the Drosophila cytoplasmic dynein heavy chain. Here we report the first evidence that P-loop-3 function is essential for dynein function. Significantly, our results further show that P-loop-3 function is required for the ATP-induced release of the dynein complex from microtubules. Mutation of P-loop-3 blocks ATP-mediated release of dynein from microtubules, but does not appear to block ATP binding and hydrolysis at P-loop 1. Combined with the recent recognition that dynein belongs to the family of AAA ATPases, the observations support current models in which the multiple AAA domains of the dynein heavy chain interact to support the translocation of the dynein motor down the microtubule lattice.